2021
DOI: 10.5114/hm.2021.106164
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the kinematics of back squats performed with different heel elevations

Abstract: Purpose. Back squat (BS) is a popular exercise owing to its capacity to develop lower limb strength. During BS, trunk incli nation and knee range of motion (roM) are relevant aspects of a proper technique, and these movement kinematics parameters can be positively altered with official weightlifting shoes lifting the heel 13 mm above the ground. Wedges are a lowcost alternative to lifting the heel to different heights, but movement kinematics adaptations with higher elevations, above 25 mm, are not well descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although it is widely believed that elevating the heel during the barbell squat might result in a more upright trunk to prevent back injury, the current findings suggest that heel height only has little effect on hip flexion angle [ 20 , 23 , 24 , 58 ] and no statistically significant effect on hip and lower back muscle activation was found [ 58 ]. Notably, although raising the heel had little effect on the hip flexion angle during the barbell squat, the tilt angle of the trunk decreased with heel elevation in the study by Monteiro et al [ 17 ]. This may result in a biomechanical transfer from the hip joint to the knee joint, contributing to the increased knee moment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although it is widely believed that elevating the heel during the barbell squat might result in a more upright trunk to prevent back injury, the current findings suggest that heel height only has little effect on hip flexion angle [ 20 , 23 , 24 , 58 ] and no statistically significant effect on hip and lower back muscle activation was found [ 58 ]. Notably, although raising the heel had little effect on the hip flexion angle during the barbell squat, the tilt angle of the trunk decreased with heel elevation in the study by Monteiro et al [ 17 ]. This may result in a biomechanical transfer from the hip joint to the knee joint, contributing to the increased knee moment.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, participants were all wearing uniform footwear to control these factors and received instruction from the same coach not associated with the study. In a recent study [ 17 ], Monteiro et al observed that the ROM of the knee joint increased with heel elevation during the barbell squat. Still, the difference in knee mobility was only statistically significant when the heel was elevated by 5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation